1998
DOI: 10.1116/1.581485
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual stress and film thickness on crystallographic orientation in Al thin films deposited by bias sputtering

Abstract: Al thin films with various residual stress and film thickness were deposited by bias sputtering. Residual stress and relative intensity of the (200) to (111) plane of Al thin films were measured by x-ray diffraction. When film thickness is fixed at 1 μm below the residual stress of ∼80 MPa, Al thin films have a (111) orientation, but above this stress, a (100) orientation. If Al thin films are in the high residual stress of ∼145 MPa, crystallographic orientation changes to a (100) from a (111) orientation as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the next section we propose a physical model to explain this correlation and the observed relationship between ion impact energy and intrinsic stress. Figure 4 shows a schematic diagram summarising the trends in stress observed as a function of ion impact energy in the three systems we have studied as well as in other reports where stress was measured as a function of incident ion energy [15,16]. In addition to this seemingly universal trend of stress with ion energy there also seems to be a strong correlation of microstructure with the stress and hence ion energy.…”
Section: Effects On Microstructure and Preferred Orientationmentioning
confidence: 78%
“…In the next section we propose a physical model to explain this correlation and the observed relationship between ion impact energy and intrinsic stress. Figure 4 shows a schematic diagram summarising the trends in stress observed as a function of ion impact energy in the three systems we have studied as well as in other reports where stress was measured as a function of incident ion energy [15,16]. In addition to this seemingly universal trend of stress with ion energy there also seems to be a strong correlation of microstructure with the stress and hence ion energy.…”
Section: Effects On Microstructure and Preferred Orientationmentioning
confidence: 78%
“…The free surface energy and the strain energy also have influences on the grain orientation [37], which is one of the primary causes of the anisotropy of a thin film. Zhang et al [38] calculated the surface energy of each lattice plane of bcc metals and indicated that the order of crystal face regarding the surface energy is E (110) < E (211) < E (100). The total energy in a thin film is the sum of the surface energy and the strain energy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [38] calculated the surface energy of each lattice plane of bcc metals and indicated that the order of crystal face regarding the surface energy is E (110) < E (211) < E (100). The total energy in a thin film is the sum of the surface energy and the strain energy [38]. Moreover, the surface energy is the majority for thinner films and strain energy is the majority for thicker films.…”
Section: Discussionmentioning
confidence: 99%